Fuel subsidy removal and performance of SMEs in Anambra State Nigeria - Ikechukwu, Eruka Cosmas; Nwagbala, Stella Chinelo; Ezeanokwasa, Francisca Nkiruka (Goodwood Publishing, 2025)
Purpose: The decision by the government to rightly remove the subsidy on fuel has caused conflict and controversies. This study examines the effect of fuel subsidy removal and the performance of SMEs in Awka, Anambra State. Method: The study adopted a survey research design, and data was collected with the aid of a questionnaire. The population of the study consists of 357 respondents randomly selected from four Small and Medium Enterprises in the Awka south local Government Area. The hypotheses were tested using simple linear regression. Results: The findings revealed that Fuel Subsidy removal significantly affects the cost of living and transport fare in the Awka South Local Government Area. Conclusions: It was concluded that the removal of fuel subsidies has led to a significant increase in transport fares and cost of living, particularly in local government areas of Nigeria and recommended that government should invest in vehicles that do not depend on fuel. Limitations: The study encountered drawbacks and limitations due to the uncooperative attitude of the respondents, who refused to fill out the questionnaire and some returned it without filling it. The problem was mitigated by revisiting and convincing them of the need to assist in completing the questionnaire. Contribution: The findings of this study will offer valuable insights that advance our understanding by employing rigorous statistical analysis. Research has quantified the short-term and long-term effects of subsidy removal on inflation, highlighting how fuel price hikes influence transportation, food prices, and household expenses.